The effect of implant neck microthread design on stress distribution of peri-implant bone with different level: A finite element analysis - Zhi-Heng Jin; Meng-Dong Peng; Qing Li (Elsevier, 2020)
Background/purpose: Significant research has proposed that the implant with microthread in the neck can significantly reduce marginal bone loss, but whether it is consistent in the condition of marginal bone loss is still unknown. The objective of this study is to investigate the effect of microthread on stress distribution in peri-implant bone with different bone level using finite element analysis. Materials and methods: A series of computational models of mandible segments with different bone resorption and implant models with or without microthread in the neck was installed by computer-aided design software. The simulated occlusal force of 150N was applied buccolingually on the top center point of implant. The FEA was performed, and the von Mises stress, principal stress and shear stress in peri-implant bone were recorded and analyzed. Results: In all models, the T-neck group exhibits higher von Mises stress and principal stress, as well as lower shear stress than S-neck group. Three types of stresses increase with the depth of bone resorption developed, but the differences of shear stress between two groups of implants were gradually decreased. Conclusion: The micro-thread design in implant neck can reduce marginal bone loss by decreasing shear stress in peri-implant bone, but this effect is gradually weakened with the decline of the marginal bone level.